Pemanfaatan Media E-Learning Moodle Untuk Menunjang Pembelajaran Mahasiswa di Fakultas Manajemen dan Bisnis Universitas Ciputra - Carol Natasia Sarigodbless Simanjuntak; Durinta Puspasari (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2020)
AbstrakVery rapid technological developments in this current era of globalization provide so many benefits in many social aspects. The use of the technology is used by the humans to facilitate every humans job. The development of technology does not only help humans in the industrial field, but also in education. This is done so that future generations are not left behind and can help to build a nation's progress. The purpose from thid study was to analyze the use of moodle e-learning media to support student learning at the Faculty of Management and Business at Ciputra University. This type of research is a qualitative descriptive study conducted at the Faculty of Management and Business at Ciputra University. Data collection techniques are done by conducting interviews and documentation. While the data analysis techniques go through several steps, namely: data collection, data reduction, data presentation, and drawing conclusions or verification. The results show that: 1) moodle e-learning media is considered interactive because it has features that make interaction between students and lecturers more enjoyable, especially as mentioned earlier that with the help of an application called 'zoom' then activities such as video conferencing can done anywhere, and not only that they can also make presentations or do quizzes, exams, and other activities that are usually done in class; 2) the use of moodle e-learning media is indeed very easy, mainly used as a learning medium as a helper or substitute for learning activities in class, in the sense that activities in the classroom can still be done even if the lecturer or student are not in the same area, but still, the lecturer able to provide material and students can also continue to receive material from lecturers even though they are outside the classroom.